PROFESSIONALLY ORIENTED TEACHING OF FOREIGN LANGUAGE WRITING OF ENGINEERING STUDENTS - Bryntseva , O. (Problems of Engineer-Pedagogical Education, 2021)
The objective of the article is to design a teaching process aimed at developing and enhancing foreign language writing skills of engineering students of higher education institutions. The article highlights that nowadays there are a sufficient number of developed teaching models on foreign language at higher technical institutions, however, in practice; the level of development of communicative competence of engineering students in written language is much lower than the level of the given competence in spoken language. Therefore, little attention has been paid to professionally oriented teaching of foreign language writing of engineering students at higher education institutions, stimulating actively seeking better ways to improve the methods, ways and means of professionally oriented teaching of foreign language writing of engineering students at higher educational establishments. The technique of scientific text abstracting and annotation in foreign language have been presented, its peculiarities and language difficulties, occurring in this process, have been defined in this article. The given recommendations concerning to foreign professional texts working can consider as supplementary means to optimize the process of foreign language training, oriented to further development forms and methods of given academic problem, they will be able to create the favorable conditions for technical and liberal education combining, to promote the students’ identity development, to acquaint with modern tendencies of techniques, industry development of studied language country. The didactic potential of blog-technologies have been analyzed; the systematic algorithm to develop linguistic students’ writing skills by the example of Internet discussion through weblog has been proposed in the work. The article concluded that the writing language learning, aimed at quick and effective perception of educational material (general and professional vocabulary), gives engineering students the opportunity to increase the strength and reliability of the educational material understanding, improve spoken language and reading, develop memory and logical thinking and upgrade the creative material in practice. Therefore, the relevance of writing language should be taken into consideration not as an additional to spoken language, but as a complex and autonomous speech skill in the context of English teaching for specific purposes at higher technical education institutions.